DISKRESI PENYIDIK POLRI TERHADAP TINDAK PIDANA YANG DI SELESAIKAN DILUAR PENGADILAN - rudin suprianto (Program Studi Magister Ilmu Hukum Universitas Kader Bangsa, 2021)
In certain situations, a police officer must be able to make the right decision or better known as discretion. The quick and precise decision is of course based on a consideration and is accompanied by accountability. The implementation is also relatively more from the subjective opinion of the police officer, however, the background of its use must of course be of a larger and broader interest. Investigators in carrying out investigative activities have discretionary authority which is protected by law, to avoid imprisonment. To find a solution to the settlement of cases of children as perpetrators of criminal acts, especially theft in the family by using Police Discretion, Restorative Justice and Diversion, so that they can be resolved without a judicial process and the sanctions applied do not absolutely have to be in the form of imprisonment. In this study to examine the implementation and effectiveness of Police Discretion in solving the problem of criminal acts outside the Court, especially theft by children in the family and how the legal arrangements regarding criminal acts outside the Court, especially theft by children in the family. This research is a normative research. The legal materials studied include primary materials consisting of statutory regulations, and secondary legal materials sourced from legal books (text books), legal journals, papers or views of legal experts contained in the mass media, dictionaries and encyclopedias, and Internet. The results of this study indicate that this authority is needed by the National Police to resolve cases that are light in nature, simple and the economic loss is relatively small. Although there is already a Supreme Court regulation Number 2 of 2012 concerning Adjusting the Limits of Minor Crimes and the Amount of Fines in the Criminal Code, minor theft crimes cannot necessarily be resolved by Restorative Justice, because Perma Number 2 of 2012 only regulates the adjustment of the limits on the value of losses and compensation. Minor criminal offenses and the Perma are only applicable internally to the Supreme Court of the Republic of Indonesia.